VI - PRIMEIROS PASSOS - Alberto Deodato; Amilcar de Castro; Mário Casassanta; Orlando Magalhães Carvalho; Gerson de Brito Mello Boson (Revista da Faculdade de Direito da Universidade Federal de Minas Gerais, 2014)
.